Rescue therapy for local tumor progression after radiofrequency ablation of small hepatocellular carcinoma: A comparison between repeated ablation and transcatheter arterial chemoembolization - Cha, Dong Ik; Lee, Min Woo; Ahn, Soo Hyun; Song, Kyoung Doo; Kang, Tae Wook; Sinn, Dong Hyun; Rhim, Hyunchul (British Journal of Radiology, 2023)
Objective: To compare the therapeutic outcomes of repeated radiofrequency ablation (RFA) and transcatheter arterial chemoembolization (TACE) as rescue therapy for the treatment of local tumor progression (LTP) after initial RFA for hepatocellular carcinoma (HCC). Methods: This retrospective study evaluated 44 patients who had LTP as initial tumor recurrence after RFA and underwent repeated RFA (n = 23) or TACE (n = 21) for local disease control. Local disease control and overall survival rates were evaluated using the Kaplan-Meier method. A Cox proportional-hazards regression model was used to identify the independent prognostic factors. The local disease control rate after the first rescue therapy and the number of rescue therapies applied until the last follow-up were also evaluated. Results: Local disease control after rescue therapy for LTP was significantly higher with repeated RFA than with TACE (p < 0.001). Treatment type was a significant factor for local disease control (p < 0.001). The overall survival rates after rescue therapy were not significantly different between the two treatments (p = 0.900). The local disease control rate after the first rescue therapy was significantly higher with RFA than with TACE (78.3% vs 23.8%, p < 0.001). The total number of rescue therapies applied was significantly higher in the TACE group than that in the repeated RFA group (median 3 vs 1, p < 0.001). Conclusion: Repeated RFA as rescue therapy for LTP after initial RFA for HCC was more efficient and had significantly better local disease control than TACE. Advances in knowledge: Even if LTP occurs after initial RFA, it should not be considered a failure of RFA, and repeated RFA should be performed over TACE if possible for more effective local disease control.
Keywords: Carcinoma, Hepatocellular; Catheter Ablation; Chemoembolization, Therapeutic; Combined Modality Therapy; Humans; Liver Neoplasms; Neoplasm Recurrence, Local; Radiofrequency Ablation; Retrospective Studies; Treatment Outcome